2021
DOI: 10.1111/idh.12520
|View full text |Cite
|
Sign up to set email alerts
|

Clinical comparison of instrumentation systems for periodontal debridement: A randomized clinical trial

Abstract: Objective To compare clinical efficacy, chairside time and post‐treatment hypersensitivity of four instruments used for subgingival periodontal debridement. Materials & Methods Seventeen patients with stage II and III periodontitis were enrolled in this randomized clinical trial using a split‐mouth design. Quadrants were randomly divided into four treatment groups: Group A: Gracey curettes‐Hu‐Friedy®; Group B: piezoelectric ultrasonic (Satelec®) with No.1S insert; Group C: diamond burs 40 µm (Intensiv Perioset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…The use of the latter can signi cantly reduce the needed time, with reductions of up to 50% 15 . These results are consistent with other studies and indicate that, in comparison to manual instruments, ultrasonic instruments can statistically decrease treatment time by over 30% 13 .…”
Section: Discussionsupporting
confidence: 93%
“…The use of the latter can signi cantly reduce the needed time, with reductions of up to 50% 15 . These results are consistent with other studies and indicate that, in comparison to manual instruments, ultrasonic instruments can statistically decrease treatment time by over 30% 13 .…”
Section: Discussionsupporting
confidence: 93%
“…It is well known that the goal of typical nonsurgical periodontal treatment is to remove biofilm to create the ideal environment for efficient bacterial plaque management [5,68,69]. Historically, scaling and root planing with manual instrumentation has been the most commonly used method of root surface debridement, with both clinical and microbiological benefits [70][71][72], as demonstrated by the studies included in this review [19][20][21][22][23][24][25][26][27]. Manual instrumentation also appears to be more effective in reducing the probing depth in moderate and severe periodontal pockets, according to Zhang et al, although no particular statistically significant differences were found with ultrasonic instrumentation [64].…”
Section: Discussionmentioning
confidence: 99%
“…According to the studies included in the review [19][20][21][22][23][24][25][26][27], there was no statistically significant differences between the treatments proposed, demonstrating the achievement of clinical outcomes with the use of ultrasonic scalers and hand instruments. These results are consistent with previous research [64][65][66][67].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations